2015
DOI: 10.1186/1546-0096-13-s1-p113
|View full text |Cite
|
Sign up to set email alerts
|

MEFV gene methylation pattern analysis in familial Mediterranean fever patients with altered expression levels

Abstract: Ulum et al.: MEFV gene methylation pattern analysis in familial Mediterranean fever patients with altered expression levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For instance, neutrophils from FMF patients showed a lower level of MEFV gene expression compared with healthy donors, although there were no methylation differences [144]. Therefore, although DNA methylation could have a function in FMF pathology by altering the expression of pyrin, more precise studies are needed to determine its exact role.…”
Section: Familial Mediterranean Fevermentioning
confidence: 99%
“…For instance, neutrophils from FMF patients showed a lower level of MEFV gene expression compared with healthy donors, although there were no methylation differences [144]. Therefore, although DNA methylation could have a function in FMF pathology by altering the expression of pyrin, more precise studies are needed to determine its exact role.…”
Section: Familial Mediterranean Fevermentioning
confidence: 99%
“…However, this hypothesis was not confirmed due to inconsistencies in findings linking MEFV methylation and disease severity. For instance, a study conducted by Ulum et al (2015) on Turkish children diagnosed with FMF revealed that there is no correlation between the methylation of the MEFV gene and the clinical symptoms presented by the patients [ 37 ]. The same research showed that patients homozygous for the M694V mutation had lower MEFV gene expression than patients heterozygous for the same mutation, thus suggesting the involvement of other epigenetic factors in the clinical picture of FMF.…”
Section: Dna Methylationmentioning
confidence: 99%